Seasonal variations in training load, sleep parameters, and hormonal markers in collegiate male rowers during the off-season - Iguchi, J.; Takimoto, M.; Kuzuhara, K.; Hojo, T.; Fujisawa, Y. (Sports, 2025)
Background: Adequate sleep is essential for recovery and performance in athletes. Internal and external training loads closely relate to sleep, but few studies have examined their distinct off-season effects. This study investigated the relationships among training load, hormonal markers, and sleep parameters in collegiate male rowers.